Lobular panniculitis in rheumatic diseases: the authors’ own data - O. N. Egorova; B. S. Belov; S. G. Radenska-Lopovok (Современная ревматология)
Objective: to study the clinical and laboratory features of lobular panniculitides (LPn) on a cohort of patients referred to the rheumatology center.Patients and methods. The investigation enrolled 687 patients (613 women and 74 men; mean age, 39.7±11.3 and 41.2±12.5 years, respectively) with panniculitis (Pn) who had received outpatient and/or inpatient treatment for diagnosed erythema nodosum or panniculitis at the V.A. Nasonova Research Institute of Rheumatology in 2007–2017.Results and discussion. By applying the diagnostic algorithm developed by the authors and the existing classification of Pn, the investigators diagnosed septal Pn in 430 (62.6%) patients and LPn in 249 (36.2%). The latter was associated with rheumatic diseases (RDs) in 97 (39%) patients. Most (70%) cases were patients with idiopathic LPn (ILPn), which, according to the 10th edition of the International Classification of Diseases, belongs to a group of systemic connective tissue disorders (M35.6), as well as those with systemic lupus erythematosus (SLE) (11.45%), dermatomyositis (DM) (9.37%), and rheumatoid arthritis (7%). This group showed a preponderance of females (the ratio of males to females was 1:7) with the chronic course of the disease mainly in ILPn. The clinical picture corresponded to four types of LPn, which may be of diagnostic and prognostic value in RDs.Conclusion. This investigation confirmed the relevance of studying LPn in RDs because of its negative impact on the course, severity and therapeutic efficiency of the underlying disease.